The correlation between the media usage, physical activities and nutritional approach for Romanian students - Trandafir, Marius; Savu, Catalin Vasile; Gheorghiu, Aurelian; Serea, Cristian; Barna, Octavian (Progress in Nutrition, 2020)
The purpose of the present study was to determine the relationship between the media usage, physical activities (PA) and nutritional approach for Romanian students in the Eastern part of Romania, from Galati County. The cross-sectional study design was designed for this purpose in order to achieve the objectives. A total of 1143 subjects, male and female students aged between 19 ± 25 years old, answered self-reported anonymous questionnaires about their usage of the media in a typical week (from Monday to Sunday) (watching TV, computers or PC games). Also, the IPAQ questionnaires were designed to assess their physical activities (in which median values of combined activities were expressed in the metabolic equivalent task (MET)·minute/week) and a self-reported anonymous Diet History Questionnaire III was created to establish their food habits quantified in Healthy Eating Index (HEI) 2015 score. Anthropometric measurements were used to calculate the body mass index (BMI) of the subjects. Within this study, randomly selected different subgroups of 212 subjects, male and female students, with the same age, between 19 ±25 years old also participated in an ancillary similar study with a set of questionnaires and interviews about their time of viewing TV or using other ways of media, (e.g.: computers, PC games, etc.), and the physical activities and nutritional habits that they have during this time. In the main study, it was found the decrease of the number of hours allocated for TV or other forms of media, from 24.3 h/week to 13.6 h/week which was associated with the increase of physical activities of the male students from 386 MET to 5347 MET, and for female students, there was an increase in physical activity from 346 MET to 4525 MET. In terms of nutritional habits, there was an increase in the HEI index from 51.3 to 56.7 for male students and from 51.6 to 55.8 for female students. The BMI index fell from 25.12 to 21.18 for male students and from 26.32 to 20.64 for female students. The cross-sectional study of the results showed a correlation between media usage, PA and nutritional approach (p≤ 0.05). The statistical analysis showed that there are strong positive correlations between the indices calculated in the main study and in the ancillary study.